The Influence Of Authentic Leadership On Employee Performance Through Organizational Culture at PT. Semen Kupang Nusa Tenggara Timur - Araujo, Betlemia Fatima De; Osijo, Immanuel Ustradi; Zainuddin, Ahmad; Sumunu, Trenggono; Handayani, Sari (Abadi Institute, 2025)
This study aims to analyze the influence of authentic leadership on employee performance through organizational culture at PT. Semen Kupang in East Nusa Tenggara. Authentic leadership is defined as a leadership style that is based on authenticity, transparency, and strong ethics, which is expected to improve employee performance. This study uses a quantitative approach with a survey method to collect data from employees of PT. Semen Kupang. The research instrument is in the form of a questionnaire that has been tested for validity and reliability. The data obtained was analyzed using path analysis techniques to see the direct and indirect relationships between authentic leadership variables, organizational culture, and employee performance. The results of the study show that authentic leadership has a positive and significant influence on employee performance, both directly and through the mediation of organizational culture. These findings indicate that authentic leadership not only improves employee performance directly but also reinforces a positive organizational culture, which in turn improves overall performance. This research makes an important contribution to the leadership and management literature, as well as provides practical implications for companies in developing effective leadership strategies and organizational culture to improve employee performance.